ChemInform Abstract: One‐Pot Synthesis of 3, 5‐Disubstituted Isoxazoles from Propargylic Alcohols Through Propargylic N‐Hydroxylamines. Issue 15 (25th March 2013) - Reddy, Chada Raji; Vijaykumar, Jonnalagadda; Jithender, Enukonda; Reddy, Gangireddy Pavan Kumar; Gree, Rene
Abstract A mild and efficient synthesis of propargylic N‐hydroxylamines from propargylic alcohols is described and successfully extended to a one‐pot synthesis of 3, 5‐disubstituted isoxazoles.